Promotion Effect of La3+ on the Catalytic Activity of Horseradish Peroxidase in vitro - Wang, Shun; Guo, Shaofen; Zhang, Guangna; Cao, Lu; Tian, Zhonghe (Asian Journal of Chemistry, 2015)
In this paper, the promotion effect of La3+ on the catalytic activity of horseradish peroxidase was investigated in vitro by using the combination of cyclic voltammetry, ultraviolet-visible, atomic force microscopy, high performance liquid chromatography and inductively coupled plasma mass spectrometry. The results indicated that the low concentration of La3+ could promote the catalytic activity of horseradish peroxidase by changing the secondary structure or the conformation of horseradish peroxidase and loosing the tertiary structure of the horseradish peroxidase and/or acting as an activator. La3+ could lead to the decrease in planarity of the porphyrin cycle in heme group, thus the exposure extent of heme Fe(III) is increased, the electron transfer is convenient and thus horseradish peroxidase catalytic activity is promoted, but La3+ did not bind with horseradish peroxidase. Therefore, there exists a weak interaction between La3+ and horseradish peroxidase in vitro. The result could provide a reference point on better understanding in agricultural application of rare earth elements.